Malaria model with stage-structured mosquitoes - Jia Li (Mathematical Biosciences and Engineering)
A simple SEIR model for malaria transmission dynamics is formulated asour baseline model. The metamorphic stages in the mosquito population arethen included and a simple stage-structured mosquito population model isintroduced, where the mosquito population is divided into two classes, withall three aquatic stages in one class and all adults in the other class, to keepthe model tractable in mathematical analysis. After a brief investigation ofthis simple stage-structured mosquito model, it is incorporated into thebaseline model to formulate a stage-structured malaria model. A basicanalysis for the stage-structured malaria model is provided and it is shownthat a theoretical framework can be built up for further studies on the impactof environmental or climate change on the malaria transmission. It is alsoshown that both the baseline and the stage-structured malaria modelsundergo backward bifurcations.